Cost‐effectiveness analysis of sofosbuvir and velpatasvir in chronic hepatitis C patients with decompensated cirrhosis. Issue 2 (15th November 2020) - Chan, Jocelyn; Kim, John J.; Barrett, Brett K.; Hamadeh, Abdullah; Feld, Jordan J.; Wong, William W.L.
Abstract: Background: Current literature indicates that direct‐acting antivirals (DAAs) are cost‐effective to treat compensated cirrhotic patients with hepatitis C. Although already funded by public payers, it is unknown whether it is economical to reimburse DAAs within the more advanced decompensated cirrhosis population. Methods: A state‐transition model was developed to conduct a cost‐utility analysis of sofosbuvir‐velpatasvir (SOF/VEL) plus ribavirin regimen for 12 weeks. The evaluated cohort had a mean age of 58 years and Child‐Turcotte‐Pugh (CTP) class B cirrhosis with decompensated symptoms. A scenario analysis was performed on CTP C patients. We used a payer perspective, a lifetime time horizon and a 1.5% annual discount rate. Results: While SOF/VEL plus ribavirin treatment for 12 weeks increased costs by 156 676, it provided an extra 4.00 quality‐adjusted life years (QALYs) compared to best supportive care (no DAA therapy). With an incremental cost‐effectiveness ratio of 39 169 per QALY, SOF/VEL plus ribavirin was determined to be cost‐effective at a willingness to pay of 50 000 per QALY. SOF/VEL reduced liver‐related deaths and reduced progression to CTP C cirrhosis by 20.4% and 21.9%, respectively. On the contrary, SOF/VEL regimen resulted in increases in liver transplants and hepatocellular carcinoma (HCC) by 54.0% and 42.5%, respectively. Similar results were found for CTP C patients. Conclusion: This analysis informs payers that SOF/VEL should continue to be reimbursed in decompensated hepatitis C patients. It also supports the recommendations by the American Association for the Study of Liver Diseases to continue screening for HCC in decompensated cirrhotic patients who have achieved sustained virologic response.